1974
DOI: 10.1093/nar/1.10.1305
|View full text |Cite
|
Sign up to set email alerts
|

A simplified method for study of RNA conformation - reaction of formylmethionine transfer RNA with [14c]methylamine-bisulfite

Abstract: A new chemical method for radioactive labeling of single-stranded regions of RNA has been used to probe the three-dimensional structure of E. coli tRNA(fMet) in solution. The procedure involves conversion of cytosine residues to N(4)-[(14)C]methylcytosines by treatment with (14)CH(3)NH(2) and sodium bisulfite at pH7. Ribonuclease digestion of the modified tRNA produces (14)C-labeled oligonucleotides which comigrate with the corresponding unlabeled oligonucleotides, facilitating structural analysis. By this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…A plot of the number of side chains attached to tRNAfMet vs. methionine acceptor activity shows that the tRNA containing derivatives of type IIb can be aminoacylated to a greater extent than those containing adducts Ia ( Figure 6). The sites of the modified cytidine residues in tRNAfMet are the same as those previously observed to be deaminated by treatment with sodium bisulfite alone at pH 6 (18) and to undergo transamination with methylamine in the presence of bisulfite at pH 7 (19). These include the unpaired cytidine at the 5' terminus, two cytidine residues in the dihydrouridine loop, the cytidine in the wobble position of the anticodon, and the two cytidine residues in the 3' terminal CCA sequence.…”
Section: Reaction Of E Coli Trnafmet With Bifunctional Aminessupporting
confidence: 62%
“…A plot of the number of side chains attached to tRNAfMet vs. methionine acceptor activity shows that the tRNA containing derivatives of type IIb can be aminoacylated to a greater extent than those containing adducts Ia ( Figure 6). The sites of the modified cytidine residues in tRNAfMet are the same as those previously observed to be deaminated by treatment with sodium bisulfite alone at pH 6 (18) and to undergo transamination with methylamine in the presence of bisulfite at pH 7 (19). These include the unpaired cytidine at the 5' terminus, two cytidine residues in the dihydrouridine loop, the cytidine in the wobble position of the anticodon, and the two cytidine residues in the 3' terminal CCA sequence.…”
Section: Reaction Of E Coli Trnafmet With Bifunctional Aminessupporting
confidence: 62%
“…Figure 1 shows the results of cytosine-specific methylation protection experiments. E. coli tRNA™" contains six cytosines that react readily with single strand specific reagents: C,, C16, C17, C34, C74, and C75 (Goddard & Schulman, 1972;Chang, 1973;Schulman et al, 1974). We were unable to determine whether Cj was reactive with dimethyl sulfate using 3'-32Plabeled tRNA™"; however, the other cytosine residues were methylated as expected in the absence of methionyl-tRNA synthetase.…”
Section: Resultsmentioning
confidence: 91%
“…Under what circumstances is the tertiary structure of tRNA present in solution? From the chemical reactivity studies (see Robertus et al 1974;Schulman et al 1974;Rhodes, 1975) and *H NMR of hydrogenbonded protons, it is reasonable to identify the form of tRNA, in the presence of excess Mg 2+ , neutral pH and low temperature, with the X-ray model. In the absence of Mg 2+ it is found that the stability of this structure is diminished, although in the presence of c. 0-2 M-NaCl the tertiary structure is present (Cole, Yang & Crothers, 1972).…”
Section: Iq 77)-mentioning
confidence: 99%